Opportunities and threats for regional development in contemporary socio-economic space - Miszczak, Katarzyna (Szanse i zagrożenia rozwoju regionów we współczesnej przestrzeni społeczno-ekonomicznej, 2020)
The current regional development models emphasize the mobilization of internal location potential, which is to be the source of the competitive advantage of spatial systems. Commonly implemented related concepts of learning regions, innovation clusters or creative sectors illustrate the new development capabilities of regions, simplifying or hindering self-renewal in a globalized, specific civilization system. The research purpose is to identify and characterize potential opportunities and possible development problems of regions that, operating in a highly diverse and rapidly changing socio-economic space, face the resolution of numerous dilemmas. One of the important conclusions presented in the article is the statement that the early building of appropriate potential and structural, organizational, methodological, scientific facilities and an own development programme is a condition for ensuring a significant competitive position for the region
Biblioteka Regionalisty, 2020, Nr 20, s. 90-108
Keywords: socio-economic space; regional policy; threats and opportunities for regions; przestrzeń społeczno-gospodarcza; polityka regionalna; szanse i zagrożenia dla regionów